Cost of Illness Trends of Schizophrenia from 2010 to 2022: A Systematic Review (Journal of Pharmaceutical Negative Results, 2022)
Background: Schizophrenia is a severe and complicated mental disorder that often manifests early and is accompanied by cognitive or behavioural abnormalities. It severely affects the patient's family and the surrounding community. All costs associated with schizophrenia, including direct medical costs, direct non-medical costs, and indirect costs, are considered in this systematic review.Objectives: This research aimed to conduct a systematic review of the recently published cost of illness articles on Schizophrenia from 2010 to 2022. Besides, it aimed to compare the direct medical and non-medical costs and indirect costs of Schizophrenia across several countries.Methods: Electronic databases were searched, including PubMed, EMBASE, Web of Science, PsycINFO, OpenSIGLE, Wiley Online, and Science Direct. This research adopted Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to document systematic reviews. Search tactics are developed concerning schizophrenia using the health economics terms such as cost analysis, direct medical costs, hospital cost, and indirect costs.Results: Nineteen of the articles were included because they fulfilled the established inclusion criteria. From the articles included, 36.8% (7/19) were from Asia, 31.5 % (6/19) from Europe, 21.1 % (4/19) from America, 5.2 % (1/19) from Africa, and 5.2 % (1/19) from Australia. The direct medical costs were 13.5 to 40.1 per cent of the total community cost. At the same time, the indirect costs ranged from 35.9 to 83.0 per cent. Conclusion: This review emphasizes the cost of illness articles across countries, mainly from 2010 to 2022. This review might open new horizons in practice for future schizophrenia COI studies.